More Word Smart - Edited by Princeton Review (New York Penguin Random House, 2017)
The Princeton Review s original Word Smart has helped over a million readers build better vocabularies and firm up their command of the English language. More Word Smart continues that journey of learning, with over 800 additional words.
Keywords: Vocabulary -- English language--Pronunciation -- SAT (Educational test)